Agile contracts : creating and managing successful projects with Scrum - Opelt, Andreas (Hoboken, N.J. : Wiley, 2013)
A methodologically sophisticated, comprehensive approach to applying the Agile fixed-price contract to IT projects while maximizing customer and supplier relationships ""Interesting and necessary for IT managers and IT lawyers.""--Walter J. Jaburek, Dipl.-Ing., Dr. iur., Dr. techn. Approximately 50 percent of software developers use Scrum, an iterative and incremental development method for managing software projects and product or application development, in their work. The benefit of Scrum and other Agile methods is that they can address shifts in a large project.
Includes bibliographical references and index.
Keywords: Agile software development; Scrum (Computer software development); Computer contracts; Agile software development; Computer contracts; Scrum (Computer software development); Agile software development; Computer contracts; Scrum (Computer software development); Electronic books; Electronic books